2004
DOI: 10.1007/s00383-004-1294-4
|View full text |Cite
|
Sign up to set email alerts
|

A standardised protocol for the acute management of corrosive ingestion in children

Abstract: Oesophageal strictures developing after caustic ingestion in children are a serious problem, and several protocols to prevent stricture formation have been proposed. A prospective clinical trial was conducted for preventing strictures in caustic oesophageal burns in a single clinic, and the results are presented. All children with caustic ingestion who had oesophagoscopy for diagnosing the severity of the burn were included in the study. Eighty-one children were included in the series, with ages ranging betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
70
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 8 publications
0
70
0
3
Order By: Relevance
“…16 So me of the re se arc hers ha ve scruti ni sed whet her the pa ren tal at ti tu des co uld ha ve a ro le in ca ses of in to xi ca ti on. 4,9,11 When the sco res that the mot hers of the chil dren re ce i ved from the PA RI sca le in our study (Tab le 1) we re com pa red to the sco res re ce i ved by the mot hers of chil dren who we re in vol ved in tra u ma tic ac ci dents in the study of Kaynar and Yıl dız, and mot hers of chil dren who we re in to xi ca ted by re a son of cor ro si ve subs tan ce in ges ti on in the study of Bu ke et al, si mi lar re sults we re ob ser ved. 1,16 The re was no sta tis ti cally sig ni fi cant re la tions hip bet we en the ages of the chil dren who inges ted cor ro si ve subs tan ces and the me an sco res the ir mot hers re ce i ved from the PA RI subs ca les (Tab le 2).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…16 So me of the re se arc hers ha ve scruti ni sed whet her the pa ren tal at ti tu des co uld ha ve a ro le in ca ses of in to xi ca ti on. 4,9,11 When the sco res that the mot hers of the chil dren re ce i ved from the PA RI sca le in our study (Tab le 1) we re com pa red to the sco res re ce i ved by the mot hers of chil dren who we re in vol ved in tra u ma tic ac ci dents in the study of Kaynar and Yıl dız, and mot hers of chil dren who we re in to xi ca ted by re a son of cor ro si ve subs tan ce in ges ti on in the study of Bu ke et al, si mi lar re sults we re ob ser ved. 1,16 The re was no sta tis ti cally sig ni fi cant re la tions hip bet we en the ages of the chil dren who inges ted cor ro si ve subs tan ces and the me an sco res the ir mot hers re ce i ved from the PA RI subs ca les (Tab le 2).…”
Section: Discussionmentioning
confidence: 99%
“…Se ve ral stu di es ha ve shown that in to xi ca ti on ca ses we re mostly pre va lent among boys. 4,5,9,15,17 Ka ya alp et al as so ci a ted boy-de pen dence among in to xi ca ti on ca ses with the fre e dom gi ven to boys in the so ci ety and the pa ren tal pres su re app li ed on the girls. 4 It was se en that the re was no statis ti cally sig ni fi cant re la ti ons hip bet we en the gen der of the chil dren who in ges ted cor ro si ve subs tan ces and the me an sco res the ir mot hers re ce i ved from the PA RI subs ca le (Tab le 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations